Pendidikan Yang Membelenggu, Membebaskan dan Memperdayakan - Sri Satir (LPPM IAIN Sorong, 2016)
Dynamics flow of society continues to flow and move towards the ocean modernism community life in which an element of hope in addition to anxiety and social unrest. Global developments are happening now could be going towards positive direction and negative direction, depending on who is the most widely installed concepts, ideas, culture and values into it. In these conditions, we talk about the progress of Islamic education in Indonesia human empowerment in the arena of globalization. The era of globalization is a product of the advancement of science and technology, hence improving the quality of human resources to spur the advancement of Muslim science and technology should get priority. This is challenge for Islamic education and thinkers. So in terms of being able to convey the Islamic relation to the demands of the quality of human resources and reclaim the advancement of science and technology; and on the other side is capable of high quality printing of human resources. Please read the following article carefully.